Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

(8x + 9) + (–6x – 1)

Sagot :

Answer:

5

Step-by-step explanation:

Simplifying

(8x + 9) + -1(6x + -1) = 0

Reorder the terms:

(9 + 8x) + -1(6x + -1) = 0

Remove parenthesis around (9 + 8x)

9 + 8x + -1(6x + -1) = 0

Reorder the terms:

9 + 8x + -1(-1 + 6x) = 0

9 + 8x + (-1 * -1 + 6x * -1) = 0

9 + 8x + (1 + -6x) = 0

Reorder the terms:

9 + 1 + 8x + -6x = 0

Combine like terms: 9 + 1 = 10

10 + 8x + -6x = 0

Combine like terms: 8x + -6x = 2x

10 + 2x = 0

Solving

10 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.

10 + -10 + 2x = 0 + -10

Combine like terms: 10 + -10 = 0

0 + 2x = 0 + -10

2x = 0 + -10

Combine like terms: 0 + -10 = -10

2x = -10

Divide each side by '2'.

x = -5

Simplifying

x = -5

made by TheRealMarinette